2004
DOI: 10.4049/jimmunol.172.2.964
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Response Gene 3 Regulates Thymocyte Proliferation during the Transition from CD4−CD8− to CD4+CD8+1

Abstract: In thymocytes developing in the αβ lineage, the transition from CD4, CD8 double negative (DN) to CD4, CD8 double positive (DP) is associated with several rounds of cell division and changes in the expression of multiple genes. This transition is induced by the formation of a pre-TCR that includes a rearranged TCR β-chain and the pre-TCR α-chain. The mechanism by which the pre-TCR influences both gene expression and proliferation has not been defined. We have evaluated the role played by early growth response g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 35 publications
6
73
1
Order By: Relevance
“…We also took advantage of an Egr-3-overexpressing transgenic (Egr-3 TG) mouse. This mouse has previously been described as having lower percentages of thymic CD4 + T cells and increased percentages of thymic CD8 + and CD4 -CD8 -T cells [26]. Peripheral blood analysis of Egr-3 TG mice indicated lower CD4 + T cell percentages than in WT controls; however, 6.5 + CD4 + T cell percentages were not significantly different (data not shown).…”
Section: Enhanced Function In Egr2 -/-And Egr3 -/-T Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…We also took advantage of an Egr-3-overexpressing transgenic (Egr-3 TG) mouse. This mouse has previously been described as having lower percentages of thymic CD4 + T cells and increased percentages of thymic CD8 + and CD4 -CD8 -T cells [26]. Peripheral blood analysis of Egr-3 TG mice indicated lower CD4 + T cell percentages than in WT controls; however, 6.5 + CD4 + T cell percentages were not significantly different (data not shown).…”
Section: Enhanced Function In Egr2 -/-And Egr3 -/-T Cellsmentioning
confidence: 73%
“…In contrast, an inhibitor of NF-AT/AP-1 association could potentially promote a tolerogenic program, in part, by leaving TCR-induced expression of Egr-2 and Egr-3 intact. [25,26]. The Egr3 -/-mice and Egr3 TG mice were backcrossed onto the B10.D2 6.5 + TCR-transgenic background for at least nine and five generations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, although induction of Egr1 appeared normal in Spi-B-expressing cells, induction of Egr2 and Egr3 was impaired, as was the induction of the Egr protein target, Id3 (57). Although we have previously determined that induction of the Egr proteins is sufficient for traversal of the ␤-selection checkpoint, it should be noted that ablation of Egr3 alone partially impairs development beyond the ␤-selection checkpoint (34). Moreover, Egr2 and Egr3 are much more potent inducers of the helix-loop-helix factor, Id3, than is Egr1 (data not shown) (32).…”
Section: Mechanism Underlying Blockade Of ␤-Selection By Spi-b Overexmentioning
confidence: 99%
“…We and others have demonstrated that the Egr family of Zn 2ϩ finger transcription factors plays an important role in traversal of the ␤-selection checkpoint (32)(33)(34). To determine whether induction of the Egr proteins were perturbed by Spi-B overexpression, we performed RT-PCR Southern blots on TAC:CD3⑀ stimulated Scid.adh cells transduced with vector alone (LZRS) or with Spi-B (LZRS-Spi-B).…”
Section: Mechanism Underlying Blockade Of ␤-Selection By Spi-b Overexmentioning
confidence: 99%
See 1 more Smart Citation